Medium pressure hydrate based gas separation (HBGS) process for pre-combustion capture of carbon dioxide employing a novel fixed bed reactor - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (International Journal of Greenhouse Gas Control, 2013)
This work presents an effective medium pressure hydrate based gas separation (HBGS) process for pre-combustion carbon dioxide capture in a novel fixed bed column. 2.5 mol% propane was added to the fuel gas mixture as an additive to decrease the operating pressure of the HBGS process. Hydrate formation kinetics was investigated at three different pressures (4.5, 5.5 and 6.0 MPa respectively) and at 274.15 K. The performance of silica sand and silica gel as a medium was evaluated. In silica sand bed, multiple nucleation events were observed. In silica gel bed, the gas uptake and water conversion to hydrates was significantly low at any given driving force than that obtained in silica sand bed. Experiments at different water saturation levels (50, 75 and 100%) in silica sand bed were investigated at 6.0 MPa and 274.15 K. It was found that at 50% water saturation, gas consumed for hydrate formation and water conversion to hydrates was almost three times that at 100% saturation. Water to hydrate conversions of up to 64.3% was achieved after 4 h of hydrate formation for the 50% water saturated silica sand bed. Our study presents an opportunity to scale up the HBGS process for CO2 capture with enhanced kinetics by employing a fixed bed reactor configuration. Decomposition experiments at a driving force of Delta T of 10 K and 23K were carried out to recover the gas consumed for hydrate formation and it was found that Delta T of 23 K was sufficient to recover the hydrated gas. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Pre-combustion; Separation